Environments for multi-agent systems III third international workshop, E4MAS 2006, Hakodate, Japan, May 8, 2006 : selected revised and invited papers - E4MAS 2006 (Lecture notes in artificial intelligence, 2007)
Models, architecture, and design -- A reference architecture for situated multiagent systems -- A unified model for physical and social environments -- Exploiting the environment for coordinating agent intentions -- CArtA gO: a framework for prototyping artifact-based environments in MAS -- Mediated interaction and stigmery -- Environment as active support of interaction -- Environmental support for tag interactions -- Cognitive stigmergy: towards a framework based on agents and artifacts -- Trace signals: the meanings of stigmergy -- Regulation function of the environment in agent-based simulation -- Governing environment -- Establishing global properties of multi-agent systems via local laws -- E4MAS through electronic institutions -- Spatially distributed normative infrastructure -- Enhancing the environment with a law-governed service for monitoring and enforcing behavior in open multi-agent systems -- Applications -- Urban traffic control with co-fields -- Designing self-organising MAS environments: the collective sort case.